Generalized eruptive keratoacanthoma: proposed diagnostic criteria and therapeutic evaluation. (6th August 2013) - Nofal, A.; Assaf, M.; Nofal, E.; Alradi, M.
Abstract Generalized eruptive keratoacanthoma (GEKA) of Grzybowski is a sporadically occurring, extremely rare variant of keratoacanthoma characterized clinically by severely pruritic, generalized eruption of numerous small follicular papules, often with a central keratotic plug, and histologically by typical features of solitary keratoacanthoma. Despite the continuous addition of new case reports, no definite diagnostic criteria have been established, and an optimum treatment is not yet determined. Herein, we review the different aspects of this rare entity, including pathogenesis, clinical and histopathological features, differential diagnosis, course and prognosis. Different therapeutic approaches and their impact on the course and prognosis of the disease are also evaluated and presented. We propose two sets of diagnostic criteria to define the disease more precisely and to avoid overlapping and confusion with other types of multiple keratoacanthoma. The first set comprises constant clinical and histopathological features that almost always present in every case and the second set includes variable features that were reported in some patients, and to which any emerging finding could be added to avoid missing cases. Although different therapeutic options have been used, either as single agents or in combinations, there is no standard therapy for GEKA and the disease still represents a therapeutic challenge.